Inventory Control Analysis in Food Retail Using the Demand Driven Material Requirements Planning (DDMRP) Method: Analisis Pengendalian Persediaan pada Retail Pangan Menggunakan Metode Demand Driven Material Requirements Planning (DDMRP) - Anisah Riyanto; Iwan Vanany (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2025)
The food supply chain is an integrated system encompassing all stages, from production, processing, distribution, to public consumption. Efficiency in the food supply chain is a crucial aspect to ensure the availability, timeliness, and accessibility of staple food distribution systems such as rice. Rice requires an efficient and equitable distribution system to meet the needs of all levels of society, including Civil Servants (PNS). PT. Food Station Tjipinang Jaya, a regionally-owned enterprise (BUMD), has implemented a rice provision program for civil servants, distributed through a network of partner retail stores. This study aims to determine the optimal buffer stock amount and replenishment time for each distribution point. The case study was conducted in Surabaya City, taking into account the number of civil servants and the distribution of their residential locations. The results of this study are expected to provide strategic recommendations for planning efficient, targeted, and sustainable food logistics distribution to optimally support regional food security programs.